Mediatory roles of leukotriene B(4) receptors in LPS-induced endotoxic shock - Kwon, Sun-Young (Sci Rep, 2019)
Sepsis, a systemic inflammatory response syndrome caused by infection, is the most common disease in patients treated in intensive care units. Endotoxic shock, the most critical form of sepsis, is caused by gram-negative bacterial infection. However, the detailed mechanism of endotoxic shock remains unclear. In the present study, we observed that the production of leukotriene B(4) (LTB(4)) and 12(S)-hydroxyeicosatetraenoic acid (HETE), inflammatory lipid mediators acting on LTB(4) receptors (BLT1 and BLT2), was significantly upregulated in peritoneal lavage fluid (PF) and serum from an LPS-induced endotoxic shock mouse model. Furthermore, BLT1/2-dependent signaling pathways mediated the expression of IL-17, IL-6, and IL-1β, key cytokines for the development of endotoxic shock, via NF-κB activation in the LPS-induced endotoxic shock mouse model. Additionally, inhibition of BLT1/2 significantly attenuated inflammation and tissue damage associated with endotoxic shock and enhanced the survival rate of mice with this inflammatory complication. Together, these results suggest that LTB(4) receptors play critical mediatory roles in the development of endotoxic shock. Our findings point to LTB(4) receptors as potential therapeutic targets for the treatment of endotoxic shock.